Advances in Immunooncology and Precision Medicine in Cholangiocarcinoma - Brown, Timothy J.; Karasic, Thomas B. (Digestive Disease Interventions, 2024)
Cholangiocarcinoma (CCA) is an uncommon but morbid cancer arising from the intrahepatic or extrahepatic bile ducts. CCA is frequently asymptomatic at early stages and is often unresectable or metastatic at the time of initial diagnosis. While chemotherapy remains the mainstay of treatment for most patients with advanced disease, the addition of immunotherapy to frontline treatment has improved survival and provided an alternative to perpetual chemotherapy. Furthermore, a variety of targeted therapies have demonstrated benefit in patients with specific biomarkers including FGFR2 fusions, IDH1 mutations, HER2 overexpression, and tumor agnostic markers such as NTRK and RET fusions, among others. This review will summarize the established roles of immunotherapy, targeted therapies, and their combinations in CCA as well as treatment strategies that are under development with potential to impact clinical practice in the coming years.
Keywords: cholangiocarcinoma; biliary tract cancer; immunooncology; precision medicine